Analysis of Teachers' Classroom Management Strategies in Supporting Deep Learning within the Implementation of the Merdeka Curriculum at UPT SMP Negeri 038 Sionom Hudon Tonga - Dosma Malau; Elisamark Sitopu; Eben Haezarni Telaumbanua (Indonesian Journal on Education (IJoEd), 2026)
This study aims to analyze teachers' classroom management strategies in supporting deep learning within the implementation of the Merdeka Curriculum in a rural school with minimal facilities. The primary research problem highlights the massive gap between the high demands of the national education curriculum and factual field conditions regarding limited digital infrastructure and the severe physical fatigue of students working in fields after school. The researcher applied a qualitative method approach featuring a single case study design, collecting data through participant observation, in-depth interviews, and documentation studies. Research findings demonstrate that school leaders simplify administrative burdens to grant teaching autonomy to teachers. Furthermore, teachers manage classrooms by validating physical fatigue to foster full learning awareness (mindful). Educators also exploit rich local ecology and culture as authentic laboratories to present highly meaningful and joyful learning without relying on advanced technology. Additionally, educators implement formative evaluations instantly on the spot and eliminate homework burdens to protect students' resting rights. The main conclusion asserts that pedagogical engineering based on empathetic values successfully overcomes all educational facility limitations. Finally, the researcher recommends the education office legitimize these contextual practices, principals issue no homework policies, and teachers routinely integrate rural ecological projects into learning scenarios